ENVIRONMENTAL DISCLOSURE URGENCY: A LITERATURE REVIEW - Timotius Agung Wahono; Paskah Ika Nugroho (Kupna Akuntansi: Kumpulan Artikel Akuntansi, 2022)
The increase of public attention to environmental issues makes the companies need to be more responsible atthose matters. Environmental disclosure is a tool to meassure that responsibility. Based on the economicperpective, prior studies tried to find out the relationship beetwen voluntary environmental disclosure (VED)and economic performance, and they found various results. Another studies captured there are manyenviromental disclosure-performance gap phenomenon. Therefore, this study attemps to analyze whetherVED is neccesary or not and find out the cause of environmental disclosure-performance gap. The resultsshows that companies with bad environmental performance are recommended to release VED for creating agood image in order to defend its self from the third parties assesment, and companies with goodenvironmental performance are recommended to release VED only if it is possible to increase economicperformance. The result also shows that common causes of environmental disclosure-performance gap aregetting economic benefit as the concequences of being a environmental-friendly company without doing anygood environmental performance, besides, the company might minimize cost because environmentaldisclosure is predicited can’t give any economic benefit and avoiding loss from the accuse of the third partieswho might doubt the credibility of data and look for the company’s environmental violation that caused byproducing environmental disclosure too extensively and self-serving.